Orange maize in Zambia: Crop development and delivery experience - Simpungwe, Eliab; Dhliwayo, T.; Palenberg, M.; Taleon, Victor; Birol, Ekin; Oparinde, Adewale; Saltzman, Amy; Diressie, Michael T. (African Journal of Food, Agriculture, Nutrition and Development, 2017)
Biofortified vitamin A “orange” maize can help address the adverse health effects of vitamin A deficiency. By 2016, HarvestPlus and its partners had developed six orange maize varieties and delivery efforts have reached more than 100,000 farming households in Zambia. HarvestPlus has established the proof of concept, that vitamin A maize varieties can be developed without compromising yield levels and that these varieties can deliver sufficient quantities of vitamin A to improve nutrition. The delivery program has also shown that farmers are willing to grow orange maize varieties and consumers are willing to buy and eat orange maize products. This paper summarizes the country’s nutritional and consumer backgrounds, the crop development and release of orange maize varieties, the delivery efforts in Zambia and impact measurement. It also synthesizes lessons learned and future challenges.